PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION (Studi Kasus pada de Vins Sky Hotel Seminyak) (Forum Manajemen, 2020)
Turnover intention is a thought possessed by every employee to stop working. The purpose of this study is to determine the effect of job satisfaction partially on turnover intention, the effect of organizational commitment partially on turnover intention and the effect of job satisfaction and organizational commitment simultaneously on turnover intention. The population used in this study were all de Vins Sky Hotel, Seminyak employees, totaling to 91 employees. Data collection is done through interviews and questionnaires. The analysis technique used is the classical assumption test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-test and f test. The result of analysis shows that job satisfaction has a negative and significant effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. While simultaneously job satisfaction and organizational commitment significantly influence turnover intention.